Characterizing wolf–human conflicts in Wisconsin, USA - Erik R. Olson; Timothy R. Van Deelen; Adrian P. Wydeven; Stephen J. Ventura; David M. Macfarland (Wildlife Society Bulletin)
ABSTRACT Management of human–wildlife conflict is a critical component of wildlife conservation globally, especially for large carnivores. Understanding general patterns of conflict can guide management decisions, such as whether or not to consider lethal or nonlethal controls. We used wolf–human conflicts in Wisconsin, USA (1999–2011), to analyze the 4 main classes of conflict typically associated with large carnivores. Of 1,662 reported wolf (Canis lupus) incidents, 801 incidents were verified as wolf. Incidents varied seasonally, with animal husbandry practices and wolf energy demands, and increased over time in absolute numbers. Human safety concerns and nonhunting dog complaints were classified as residential‐, wildland‐, or farm‐associated. Human presence or intervention reduced the likelihood of dog mortality (vs. injury) following a wolf attack. Some wolf packs were primarily implicated in either hunting or nonhunting dog conflicts, with nonhunting dog attacks for the most part being attributable to lone or dispersing wolves. No complaints about aggressive behavior or wolf attacks on humans were investigated during the study period; however, wolves did approach humans at close range (median = 12.5 m) and attacked pets near homes. Wolf–human conflicts cluster spatially, which could be a way to prioritize mitigation efforts. To guide management decisions, managers should determine 1) what behaviors characterize habituated wolves; 2) what characteristics of wolf–human conflict determine whether or not human safety concerns should be considered; and 3) under what conditions should lethal control be implemented. Continued detailed reporting by investigators of wildlife complaints, especially behavioral data on wildlife, domestic animal(s), and complainant, will inform management decisions and facilitate assessment of prior decisions. © 2015 The Wildlife Society.